Knowledge of Oral Emergency Contraception Among Pharmacy Students - Bria Nikole Blake; Samantha Bookbinder; Gweneth Lazenby; Amari Marshall; Elizabeth Weed; Michelle Meglin (Women's Health Reports)
Background: Access to emergency contraception is an important consideration in preventing unintended pregnancies. Inconsistent information about emergency contraceptive given to patients at retail pharmacies may limit access. Objective: In this study, we aimed to assess pharmacy students' knowledge of oral emergency contraception. Methods: Students in a Doctor of Pharmacy program completed a confidential survey about their knowledge of and training on oral emergency contraception. Respondents self-reported demographics included age, race, ethnicity, gender, and year in pharmacy school. The survey questions assessed student knowledge of indications, availability, side effects, and mechanisms of action of oral emergency contraception, as well as their training on emergency contraception. Chi-squared and Fisher's exact tests were used to determine if demographics influenced knowledge outcomes. A multivariate logistic regression, including age, gender, ethnicity, religion, year of training, hours of education, and source of knowledge acquisition, was used to adjust for confounding variables. Results: Among 296 pharmacy students, 31% (92/296) completed the survey. Among respondents, 34% (31/92) showed adequate knowledge of oral emergency contraception based on four critical knowledge questions. Third- and fourth-year students were more likely to have adequate knowledge than first- and second-year students (odds ratio [OR], 2.70; confidence interval [95% CI], 1.07–6.80). Students who reported learning about emergency contraception through reading assignments were more likely to have adequate knowledge than students who did not report learning from reading assignments (OR, 2.09; 95% CI, 1.30–3.35). Conclusions: Most pharmacy students at a single academic center did not have adequate knowledge of oral emergency contraception. These findings highlight the need for trainings to improve pharmacy student knowledge of oral emergency contraception.